PENINGKATAN DISIPLIN GURU DALAM MENGUMPULKAN PERANGKAT PEMBELAJARAN MELALUI SISTEM REWARD DAN PUNISHMENT DI SDN 29 SUNGAI LIMAU - Maryunis Maryunis (STKIP Pesisir Selatan, 2017)
ABSTRACTBased on the observations that researchers do in the semester of January-June 2015/2016, researchers found the phenomenon that the level of discipline of teachers in collecting learning tools is still low. This is evident from the time the researcher asked the teacher to collect learning tools there are still many teachers who did not collect the requested learning tools. There are also teachers who are in a hurry to prepare learning tools when the principal or supervisor will supervise the class. Of the six class teachers, if averaged, only 60%, teachers who complement the learning tools either in the form of syllabus, SK / KD, RPP, prota promes and teaching materials. Meanwhile, 40% of teachers did not collect. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The research subjects consisted of 6 teachers of SDN 29 Sungai Limau class who were research class teachers. The data were collected using obeservation sheets. Data were analyzed using percentages. Based on the result of research, it can be concluded that the application of reward and punishment system can improve teacher's discipline in collecting learning tools. This is evidenced from before applied rewards and punishment, the percentage of teachers who collect learning tools is only 66.67% with that collects on time only amounted to 22.81%. After applied reward and punishment system, then in cycle I, teacher collecting learning device become 79,65% with percentage which collect on time is 35,79%. After cycle II, the percentage of teachers who collected learning tools became 97.54% with the percentage of teachers who collected on time was 81.05%.Keywords: Discipline, Learning Device, Reward and Punishment